Exploring preferential food selection: a cross-cultural study between Chinese and Malay undergraduates in a private university - Alias, Adila (2020)
Previous studies and cross-sectional surveys conducted in Malaysia have shown that the prevalence of obesity, diabetes and other non-communicable diseases (NCDs) are associated with poor diet practices. Overeating is contributing to the increasing prevalence of obesity and other NCDs among Malaysians. This study aims to investigate how environmental influences might impact food preferences between Malay and Chinese.